2017
DOI: 10.1002/ange.201708964
|View full text |Cite
|
Sign up to set email alerts
|

A Thermophilic Tetramolecular G‐Quadruplex/Hemin DNAzyme

Abstract: The quadruplex-based DNAzyme system is one of the most useful artificial enzymes or catalysts;t heir unique properties make them reliable alternatives to proteins for performing catalytic transformation. The first prototype of at hermally stable DNAzyme system is presented. This thermophilic DNAzyme is capable of oxidizing substrates at high temperatures (up to 95 8 8C) and long reaction times (up to 18 ha t7 5 8 8C). The catalytic activity of the DNAzymes were investigated with the standardperoxidase-mimickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Catalytic activity of G4/hemin complex can be further enhanced by loop/flanking nucleotides which act as a general acid-base during the initial step of the reaction. 31, 3436, 93 Our simulations provide solid evidence to support this model: the three-nucleotide propeller loops of 1KF1 and single slipped Gs in t13 and t45 (being positioned equivalently to flanking nucleotides) are flexible enough to form a base/hemin/quartet sandwich (Figures 4B and 5). In this arrangement, the base is close to the hemin iron atom thus being suited to bind H 2 O 2 , stabilizing the transition state of the reaction and increasing its rate.…”
Section: Discussionsupporting
confidence: 56%
“…Catalytic activity of G4/hemin complex can be further enhanced by loop/flanking nucleotides which act as a general acid-base during the initial step of the reaction. 31, 3436, 93 Our simulations provide solid evidence to support this model: the three-nucleotide propeller loops of 1KF1 and single slipped Gs in t13 and t45 (being positioned equivalently to flanking nucleotides) are flexible enough to form a base/hemin/quartet sandwich (Figures 4B and 5). In this arrangement, the base is close to the hemin iron atom thus being suited to bind H 2 O 2 , stabilizing the transition state of the reaction and increasing its rate.…”
Section: Discussionsupporting
confidence: 56%
“…The peroxidase mimicking catalytic activity of G4 DNAzyme catalyzes the oxidation of 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS 2− ) to produce a colorimetric change from a colorless solution to a visible blue-green product (see Figure 9). DNAzyme systems involving other substrates like luminol, 3,3′,5,5′-tetramethylbenzidine sulfate (TMB), 4-chloro-1-naphthol (4-CN) or scopoletin (Sc), in the presence of hydrogen peroxide (H 2 O 2 ) can also be used to produce colorimetric, electrochemical and fluorescence readouts [46,47,48,49,50,51]. However, colorimetric G4-hemin DNAzyme-based biosensors are utilized in diagnostics for its simplicity, fast analysis, low cost and most notably, the ability to detect target molecules visually.…”
Section: G-quadruplex-based Detection Systemmentioning
confidence: 99%
“…Previous studies have shown that the structure of the G-quadruplex has a crucial impact on the catalytic efficiency. For example, the DNAzyme formed by parallel G-quadruplex has a much higher catalytic efficiency than that formed by antiparallel G-quadruplex [ 6 ], and that formed by G-quadruplex with adenosine at the 3′-end shows an enhanced catalytic activity [ 7 ], while that formed with adenosines at both the 3′- and 5′-ends can efficiently catalyze the oxidation even at 95 °C [ 8 ]. Besides, two or more individual G-quadruplexes stacked on top of each other to form a multimeric G-quadruplex have a synergistic enhancement effect on the catalytic activity of the DNAzyme [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%